MAKANAN ADAT PADA UPACARA TURUN MANDI DI NAGARI PAKAN RABAA TIMIUR KECAMATAN KOTO PARIK GADANG DIATEH KABUPATEN SOLOK SELATAN - Marhayani, Marhayani; Elida, Elida; Sofnitati, Sofnitati (Faculty of Tourism and Hospitality - Universitas Negeri Padang, 2015)
This research is motivated lack of knowledge of young mothers and teens on traditional food at the ceremony down shower. The purpose research to describe the stages of the ceremony down bath, traditional food which brought the child home bako, traditional food served to guests, tools used to carry food and served customs and the meaning of indigenous foods. This type of research is a qualitative. method, Other research object is customary food down bathing ceremony, data collection techniques: observation, interviews and documentation.Data analysis techniquesis: data reduction, data display, conclusions and verification. Portrait of researt result that stages the ceremony down the shower consists of: duduak baropok, mamanggia, pai kadapua, and ceremonies baralek down shower. Traditional food at the ceremony down the bath consists of traditional food that is brought by the child home bakopisangnya and traditional food that is served to guest at the ceremony down shower. Food customarymeaning as moralmessagesthat are usefulfor thechild, and the child's family. 1 Prodi PendidikanKesejahteraanKeluargaUntukWisudaPeriodeMaret 2015 2 DosenKesejahteraanKeluarga FT UNP Keywords: Food Customs, Ceremonies Down Shower